The current status of the servant leadership and its relationship with job satisfaction from the viewpoint of faculty members at the University of Hail - Al-Azam, Miesam Fawzi Motiar (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the reality of servant leadership and its relationship to job satisfaction from the point of view of faculty members at the University of Hail. To achieve the objectives of the study, it adopted the descriptive, analytical approach as well as the questionnaire The study used the questionnaire as a tool for collecting data from the study sample, which consisted of (385) members of the university faculty, who were randomly selected from the study population. The results showed that there is a medium degree in the level of the servant leadership at the University of Hail from the point of view of the faculty members The results also showed a positive and significant relationship at sig. Attention to subordinates ranked fourth with a high evaluation degree. The study also showed a moderate degree of job satisfaction among faculty members. Based on the results, the study recommended the need to increase attention. Based on the results of the study, the researcher recommends that the University of Hail pay more attention in studying the servant leadership and how to apply, practice and benefit from it in enhancing the job satisfaction of the faculty members.
Keywords: servant leadership; job satisfaction; faculty staff members